Material Balance by Linear Equations - Seyed Mohammad Milani (Iranian Journal of Chemistry & Chemical Engineering, 1997)
Material Balance around process has been conducted by using mixer output equations. A method based on Mason's theory has been proposed to develop mixer output equations.